Tunnel Valley Genesis and Subglacial Dynamics in South-Central Ontario - Mulligan, Riley (2019)
Glacial sediments are found across formerly glaciated regions across the world and host a variety of important resources, ranging from groundwater to hydrocarbons, aggregate material, and mineral deposits. In southern Ontario, Canada, thick successions (up to 200 m) of Quaternary glacial sediments are truncated by large valleys (>30km long, 2 to >8.5 km wide, and up to 200m deep) that formed subglacially and have characteristic morphology and infill stratigraphy. These valleys are interpreted as (a new class of) tunnel valleys and strongly affect groundwater resources and flow systems at local and regional scales. The overall context of the valleys is evaluated through an introduction to the study area, objectives, and background information on subglacial systems and geologic history of south-central Ontario (Chapter 1). Interpretation of valley genesis in Simcoe County is provided through an integrated, multi-faceted approach, involving: description of the morphology and sediment infill succession within the valleys from surficial mapping, sedimentological logging of continuously-cored boreholes, and geophysical surveys (Chapter 2); delineation and characterization of seismic architecture from high-resolution lake-based sub-bottom profiles in one of the valleys (Chapter 3); detailed site-scale field description of the internal characteristics of the regional Late Wisconsin till sheet in various subglacial settings (Niagara Escarpment, uplands, lowlands; Chapter 4); comparison of the characteristics of the subglacial bed within the study area to adjacent regions in southern Ontario (Chapter 5); and a synthesis of the major findings from all the different components of this investigation and suggestions for future work to shed further light on several questions that arise from this study (Chapter 6). Together, key data from these studies of tunnel valleys and related deposits – a near-continuous till sheet on the surface of uplands and along the flanks and floors of the tunnel valleys, multi-stage ...